Influence of Contracted Extension Service Delivery Model on Uptake and Use of Cassava Technologies, Innovations and Management Practices in Nakuru and Busia Counties, Kenya - Kaburu, Purity Kinya; Kariuki, Isack Maina; Langat, Jackson (Discoveries in Agriculture and Food Sciences, 2025)
Adoption of Technologies Innovations and Management Practices (TIMPs) by farmers is critical in improving farmers’ livelihoods. The Kenyan Government, through Kenya Agricultural Productivity and Agribusiness Project (KAPAP), implemented the Contracted Extension Service Delivery Model (CESDM) across various agricultural value chains. In the cassava value chain, nine TIMPS were promoted which included the use of improved cassava planting materials, organic manure/ inorganic fertilizers, rotational crops, intercrops, pest and disease management, drying, milling, blending and collective marketing. Using a cross-sectional approach and a sample of 816 respondents, this study employed a multivariate and an ordered probit to determine the effects of CESDM on adoption of cassava TIMPS in Busia and Nakuru counties of Kenya. The results showed that the CESDM influenced certain practices positively. These included use of improved cassava varieties, crop rotation, fermentation and milling. The CESDM was negatively associated with fertilizer use, intercropping and disease control. Generally, factors that influenced adoption of cassava TIMPS included household size, land tenure, cassava yield, credit use, off-farm employment, ownership of cassava machineries, gender of household head, access to cassava information, higher cassava acreages, cassava experience and agricultural group membership. Factors that explained the extent of use of cassava included household size, gender of household head, land ownership, and age of household head. The study concluded that indeed government support and interventions are key in enhancing adoption of selected cassava TIMPs, and such initiatives are necessary in building a critical mass of trained farmers for increased welfare gains.